Implementation of green river retrofitting concept using Blockchain-BIM for cost performance - Arif, Eka Juni; Husin, Albert Eddy (SINERGI, 2024)
Considering the global climate change and anticipation of water needs, this can pose significant problems. Trees play a crucial role in mitigating climate change, with the ability to assimilate carbon dioxide (CO2) and certain air pollutants, purify rainfall, and act as a barrier against soil erosion. This research focuses on the Bekasi River, which has a length of 6 km and a cross-sectional width of 65 meters. The data used is directly extracted from project data utilized for cost estimation, and data collection is conducted through interviews and questionnaires. The research methodology integrates Structural Equation Modeling-Partial Least Squares (SEM-PLS) as a data processing tool for survey and factor identification, along with Blockchain-Building Information Modeling (BIM) to assess the cost performance improvement of environmentally friendly reinforcement. Based on the test results, the utilization of BIM combined with blockchain technology can result in cost savings of 3.69% for the Improved level, 3.72% for the Enhanced level, 4.39% for the Superior level, 4.92% for the Conserving level, and 5.17% for the Restorative level in terms of cost enhancement.